Increased cytokine secretion by human bone marrow cells after menopause or discontinuation of estrogen replacement - Bismar, Hanadi; Diel, Ingo J.; Ziegler, Reinhard; Pfeilschifter, Johannes (The journal of clinical endocrinology & metabolism, 1995)
Studies on circulating human mononuclear cells and rodents have suggested that cytokines such as interleukin-1 (IL-1) and IL-6 may be paracrine mediators of postmenopausal bone loss. However, the assumption that the concentration of these cytokines is increased in the local bone microenvironment of postmenopausal women is still unproved. To address this question, we aspirated bone marrow from the iliac crest of 40 women during surgery for localized breast cancer and analyzed cytokine release in short term cultures. Cytokine levels in the cell supernatants from premenopausal (n = 12) and late postmenopausal (n = 18) subjects were not significantly different. Bone marrow cells from women who had discontinued estrogen replacement within 1 month before aspiration (n = 5) secreted significantly more IL-1 alpha, tumor necrosis factor-alpha, IL-6, prostaglandin E2, and granulocyte-macrophage colony-stimulating factor than bone marrow cells from either premenopausal or late postmenopausal subjects. Increased levels of IL-6, prostaglandin E2, and granulocyte-macrophage colony-stimulating factor were also observed in cultures from women who were within 5 yr of natural menopause (n = 5). Our data show that estrogen withdrawal is associated with an increased potential of human bone marrow cells to release bone-resorbing cytokines and strengthen the hypothesis that these cytokines may play a role in the accelerated bone resorption after menopause.
Gesehen am 23.10.2024